Considerations for Avoiding Mafsadat in Refusal and Granting Marriage Dispensation by Kajen Religious Court Judges - Nur Ika Putri, Shafina; Siti Qomariyah (Al-Hukkam: Journal of Islamic Family Law, 2024)
Religious courts generally grant marriage dispensation to prevent harm (mafsadat). This study analyzes three decisions from the Kajen Religious Court: Numbers 209/Pdt.P/2023/PA.Kjn.,  248/Pdt.P/2022/PA.Kjn., and 185/Pdt.P/2022/PA.Kjn. Though the reasons behind each request differed, the judges used similar legal reasoning, focusing on avoiding harm. The research method used is library research with a qualitative, interactive analysis approach. The findings show that the main reasons for applying for marriage dispensation include: the couple already has a close relationship and fears doing inappropriate acts, the applicant is pregnant, or the applicant has reached puberty and feels ready for marriage. In making decisions, the judge considers legal aspects and the principle of dar’u al-mafāsid muqaddam ‘ala jalb al-maṣāliḥ (avoiding harm takes priority over gaining benefit). Applications are rejected if the applicant is deemed unready for marriage or the situation risks leading to divorce. Applications are granted when the couple already knows and loves each other deeply, cannot be separated, and delay might cause greater harm.